Ivermectina no tratamento de ratos parasitados por Strongyloides venezuelensis : efeitos sobre a motilidade gastrintestinal - Mendonça, Jalvita Cardoso (2018)
Ivermectin (IVM) is the anti-parasite of choice for strongyloidiasis and experimental models using Strongyloides venezuelensis are employed to understand the parasite-host relationship. The objective of this study was to evaluate the effects of IVM on the gastrointestinal tract of S. venezuelensis infected rats. Male Wistar rats (300-400g) were randomly assigned to: a) Control animals, uninfected and untreated (n = 5); b) Sv-Animals infected with S. venezuelensis considered parasitized control (PC) at the peak of infection (dpi), i.e.9dpi; c) Sv / IVM –Animals infected with S. venezuelensis treated with 1 dose IVM (200 μg / kg -VO) (Sv / IVM1) or treated with three doses (Sv / IVM3) at 24-h intervals, each dose being (200 μg / kg -VO); d) IVM –Animals treated with ivermectin divided into: treated one dose of ivermectin (IVM1) or three doses (IVM3). All groups, except control, were further subdivided into2groups: start of experiment (SE) (n = 5) and end of experiment (EE) (n = 5). Egg counts were measured by grams of faeces (EPG) and adult worms recovered from the intestine. The mean gastric emptying(MGET), cecum arrival (MCAT) and small intestine transit (MSITT) times were determined by methodAlternating Current Biosusceptometry (ACB). In the morphometric analyzes of histological sections of the small intestine, the thickness of the submucosa (SM), muscular circular (MCL) and longitudinal (LL) layers were evaluated. All data were submitted to statistical analysis of variance (ANOVA) followed by Dunnett with p <0.05. The Sv / IVM1 and Sv / IVM3 groups present significant reduction of EPG and worms in SE, although only the SV / IVM3 group eliminated them completely. At higher doses, IVM accelerates gastric emptying (GE) only in SE. In infected animals, IVM1 reverses the accelerated GE observed in untreated animals, while IVM3 does not modify the condition. The Svand Sv / IVM1 groups show no change in MCAT at any time, while larger doses of the drug prolong MCAT. IVM caused changes in MSITT throughout the experiment. In infected animals, IVM1 reversed the traffics lowing caused by the parasite in EE, while IVM3 accentuated it. In morphometric analysis, Sv group presented reduced LL and thicker MCL compared to controls. The Sv / IVM3 group had lower MCL compared to controls. The IVM1 group presented altered LL and the IVM3 groups howed all the narrower layers. This longitudinal muscular atrophyac counts for there duced propulsion observed in intestinal transit. Treatment with a dose of IVM reversed the motor alterations observed in other studies, although the IVM without the presence of the infection has altered parameters of the transit and gastrointestinal structure. Revisiting the action of traditional drugs broaden sknowledge in the parasite-host binomial and all accurate therapeutic strategies.